Depression, Anxiety, and Stress due to Changes in Employment Status during COVID-19 Pandemic: A Study in Badung Districts, Bali, Indonesia - Made Violin Weda Yani; Made Sindy Astri Pratiwi; Agus Indra Yudhistira Diva Putra; Ni Ketut Sri Diniari (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To determine the relationship between depression, anxiety, and stress with the employment status of people in Bali during Covid-19 pandemic.Methods: This study was a cross-sectional analytical study conducted in Bali, Indonesia, in 2021. The instrument used was DASS-21 questionnaire, which was distributed to a total sample size of 96 people. The relationship between variables were analyzed with a p-value of <0.05 as the cut-off for a significant relationship.Results: Depression symptoms had a significant relationship with gender (p=0.024) while anxiety symptoms had a significant association with the employment status during the pandemic (p=0.027). Similarly, stress symptoms also had a significant relationship with gender (p=0.007) and employment status during COVID-19 pandemic (p=0.007).Conclusion: There is a relationship between depression, anxiety, and stress due to changes in employment status during the COVID-19 pandemic in Badung Districts, Bali.